2019
DOI: 10.3389/fnins.2019.00684
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent Stem Cells for Brain Repair: Protocols and Preclinical Applications in Cortical and Hippocampal Pathologies

Abstract: Brain injuries causing chronic sensory or motor deficit, such as stroke, are among the leading causes of disability worldwide, according to the World Health Organization; furthermore, they carry heavy social and economic burdens due to decreased quality of life and need of assistance. Given the limited effectiveness of rehabilitation, novel therapeutic strategies are required to enhance functional recovery. Since cell-based approaches have emerged as an intriguing and promising strategy to promote brain repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 160 publications
(262 reference statements)
0
10
0
Order By: Relevance
“…Heat stress caused by high temperature can lead to decreased cerebral blood ow and rapid death of central nerve cells under the stimulation of high temperature and hypoxia (7). In our study, HE staining, neuron Nissl staining, and cerebellar silver staining showed that after the heat stroke injury, the hippocampal vulnerable area (CA1 area), cerebellum, neurons, cones, cerebellar (12)(13)(14). Therefore, the treatment of MSCs has an important protective effect on the common central system damage of heat stroke, and is of great signi cance for the survival rate and prognosis of heat stroke rats.…”
Section: Discussionmentioning
confidence: 57%
“…Heat stress caused by high temperature can lead to decreased cerebral blood ow and rapid death of central nerve cells under the stimulation of high temperature and hypoxia (7). In our study, HE staining, neuron Nissl staining, and cerebellar silver staining showed that after the heat stroke injury, the hippocampal vulnerable area (CA1 area), cerebellum, neurons, cones, cerebellar (12)(13)(14). Therefore, the treatment of MSCs has an important protective effect on the common central system damage of heat stroke, and is of great signi cance for the survival rate and prognosis of heat stroke rats.…”
Section: Discussionmentioning
confidence: 57%
“…MSCs have signi cant protective effects on cerebral ischemic injuries, external injury caused by brain damage, Alzheimer's disease, dementia, Parkinson's disease and other neurodegenerative diseases. The speci c mechanisms include: MSCs can secrete various neurotrophic factors, regulate immune response, improve cerebral vascular permeability, and adjust nerve cell communication (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is still no effective targeted method for treatment of heat stroke, especially for brain injury. Studies have con rmed that mesenchymal stem cells (MSCs) have a strong immune regulatory capacity, and can secret or induce the production of cytokines that have a signi cant protective effect on various brain injuries (12)(13)(14). However, the protective effect of MSCs on brain injury caused by radiation diseases has been seldom studied.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, mesenchymal stem cell (MSC)-based therapy is being considered as a potential treatment strategy for CNS injury (11)(12)(13). MSCs possess multipotent properties, such as the capacity to secrete various factors, differentiation potential, and immunoregulatory effects (14).…”
Section: Introductionmentioning
confidence: 99%